A survey of chest radiographs of migrant workers in Malaysia - Abdullah, Basri Johan Jeet (Faculty of Medicine, University of Malaya, 2002)
A survey was done to assess the chest radiographs of a selected group of immigrants. The objective is to ascertain the presence of abnormalities especially the presence of tuberculosis. Five hundred and eleven (511) chest radiographs (PA view) were evaluated. Majority of the chest radiographs were normal, except for two cases of hilar lymphadenopathy, four cases of scoliosis and cervical rib, an old case of fracture of the clavicle and a case of cardiomegaly. Only two cases of TB were detected.